Lack of effect of Maraviroc intensification on blood and gut reservoir. - Tiraboschi, J; Ray, S; Patel, K; Pace, M; Phalora, P; Robinson, N; Hopkins, E; Meyerowitz, J; Wang, Y; Davies, O; Mant, C; Cason, J; et al. (Mary Ann Liebert, 2016)
We show that intensification of treatment with maraviroc in patients chronically infected with HIV-1 receiving successful long-term ART was not associated with improvements in HIV related morbidity, HIV reservoir, microbial translocation, immune activation or immune exhaustion in either gut or peripheral blood. The measurement of reservoir in both gut and blood longitudinally contributes to a paucity of data in the area.